Resort Based Management Web GIS Towards Cyber Conservation in Indonesia - Vatresia, Arie; Sadler, Jonathan P.; Rais, Rendra Regen (Centre for Science and Technology, IAIN Surakarta, 2017)
Biodiversity loss is a global issue and is especially of pressing concern in mega diverse countries, such as Indonesia. To prevent any further catastrophe, the Ministry of Forestry and Environment of Republic of Indonesia has been promoting the resort based management to be implemented in Indonesia to maximize the performance of conservation activity. The lack of data standardization made it hard to organize and manage archipelagic country that consist 17,504 islands with no technology provision in most of them. In this paper we develop a framework of integration mobile-web technology for biodiversity and conservation in Indonesia. We introduced a new framework to maintain the biodiversity and conservation data in Indonesia.